Can LibertyLink Cotton or Soybeans Work in Florida? - Jason Ferrell; Barry Brecke; Clyde Smith (EDIS)
SS-AGR-339, a 3-page illustrated fact sheet by J. Ferrell, B. Brecke, and Clyde Smith, answers questions about the potential use of LibertyLink crops, which are genetically modified to tolerate applications of glufosinate, as part of a control strategy for Palmer amaranth control in cotton and soybeans. Published by the UF Department of Agronomy, January 2011.